The Recommendations Enhancing The Effectiveness Of Credit Risk Management For Commercial Banks In Ho Chi Minh City - Thi Hang Nga, Phan (British Journal of Marketing Studies, 2017)
In Vietnam, the commercial banks are in virtually the country and have been subject to a great deal of regulations. One of the regulations is the minimum capital commercial banks must keep absorbing loss if unexpected things happen. Besides, the credit risk is one of the most significant risks that banks face, considering that granting credit is one of the main sources of income in commercial banks. Therefore, the management of the risk related to that credit affects the profitability of the banks. The aim of the research is to provide readers with accurate information regarding factors affecting the credit risk management of commercial banks in Ho Chi Minh City and the researcher has the recommendations enhancing the effectiveness of credit risk management for commercial banks in Ho Chi Minh City. The study results showed that there were 250 managers of commercial banks in Ho Chi Minh City who interviewed and answered about 19 questions. Data collected from June 2016 to December 2016 for commercial banks in Ho Chi Minh City. The paper had been analyzed KMO test, Cronbach’s Alpha and the result of KMO analysis which used for multiple regression analysis. Managers’ responses measured through an adapted questionnaire on a 5-point Likert scale (Conventions: 1: Completely disagree, 2: Disagree, 3: Normal; 4: Agree; 5: completely agree). Hard copy and online questionnaire distributed among 1.000 managers of commercial banks in Ho Chi Minh City. In addition, the exploratory factor analysis (EFA) results showed that there were five factors, which included of factors following human resources (X1), macro environment (X2), customer (X3), technology capabilities (X4) and financial capabilities (X5) with significance level 5 percent. In addition, all of five components affecting the management of the credit risk at commercial banks in Ho Chi Minh City with significance level 5 percent. The research results processed from SPSS 20.0 software.